(untitled) (AYUSHDHARA, 2025)
Ayurveda is an Upang of Atharv veda and main aim is the maintenance of health of healthy person and curing disease of diseased person. In Sushrut Smahita, Acharya Sushrut has properly given the detailed knowledge about Raktamokshana in various diseases. It is one of the essential procedures of Panchkarma according to Sushrut Samhita. In the Raktamokshana procedure letting out the deoxygenated blood from the body is done and it is indicated in Rakta dushti and Pitta dushti conditions. There are some procedures described under Raktamokshan such as Prachchan, Shiravedha, Shringavcharan, Jalaukavacharan, Alabu and Gati. Siravedha is the Ardhchikitsa of the entire surgical management which is described in Shalya Tantra as similar Basti Karma described in Kayachikitsa. Some modern procedure like venesection/phlebotomy for laboratory blood test and iv canulation for medication and nutritional balance, cupping procedure can be correlated with Raktamokshan which is used to cure the blood related diseases, pain, inflammatory diseases etc.